Endoscopic mucosal resection of flat and sessile colorectal adenomas: Our experience with long-term follow-ups - Grgov, Saša; Dugalić, Predrag; Tomašević, Ratko; Tasić, Tomislav (Vojnosanitetski pregled, 2013)
Bacground/Aim. Endoscopic mucosal resection (EMR) or mucosectomy is a removing method of flat or sessile lesions, laterally spreading tumors and carcinoma of the colon or the rectum limited to mucosa or the surface part of the submucosa. The aim of the study was to estimate the efficacy and safety of EMR in removing flat and sessile colorectal adenomas. Methods. This prospective study involved 140 patients during the period of 8 years. A total of 187 colorectal adenomas were removed using the EMR method “inject and cut with snare”. Results. The approximate size of mucosectomised adenomas was 13.6 mm (from 8 mm to 60 mm). There was a total of 48 (25.7%) flat adenomas and 139 (74.3%) sessile adenomas, (p < 0.01). Using “en bloc” and “piecemeal” resection, 173 (92.5%) and 14 (7.5%) of colorectal adenomas were removed, respectively. In all the cases, a complete removal of colorectal adenomas was achieved. Two (1.4%) patients had adenoma removal with intramucosal carcinoma each. In the average follow-up period of 21.2 ± 17.8 months, 2 (1.4%) patients had adenoma relapse after EMR. Considering complications, there was bleeding in 1 (0.7%) patient with a big rectum adenoma removed with EMR. Furthermore, one (0.7%) patient had a postcoagulation syndrome after cecal adenoma was removed by EMR. Conclusion. EMR is an efficient, safe and minimally invasive technique of removing flat and sessile adenomas in the colon and the rectum, with a very low percentage of adenoma recurrence over a long period of monitoring.